Sustainable Human Resource Practices: The Impact of Transformational Leadership, Organizational Commitment, and Work Motivation on Job Satisfaction - Hadi Rahmanda; Yasri Yasri; Rino Rino (Indonesian Journal of Sustainability Accounting and Management, 2024)
This literature study examines the influence of transformational leadership style, organizational commitment, and work motivation on job satisfaction. This research method applies to a literature study or systematic literature review (SLR) procedure. This research data was obtained through online searches and journals related to job satisfaction published in the 2020-2023 period. The number of journals analyzed was 20 journals. The results of this literature study show that the transformational leadership style can function as a mentor who can create job satisfaction in employees through work performance and act as a friend who can create job satisfaction in employees through work relationships. Job satisfaction resulting from organizational commitment is influenced by several factors such as a good and healthy organizational culture, the active involvement of employees both structurally and culturally in the organization, and various memorable and enjoyable experiences during the organization which are conditioned by a comfortable and conducive work environment. Strong motivation for work is an internal drive that can awaken all unexplored potential to be activated in hard work, innovative work and sincere work to achieve individual job satisfaction and work success for the organization.